Co(NO3)2/covalent organic framework nanoparticles for high-efficiency photocatalytic oxidation of thioanisole. Issue 43 (9th May 2022) - Xu, Mingzhao; Zhang, Jianling; Liu, Lifei; Cheng, Xiuyan; Hu, Jingyang; Sha, Yufei; Su, Zhuizhui; Wang, Yanyue
Abstract : Co(NO3 )2 /covalent organic framework nanoparticles exhibit high activity and selectivity for the photo-oxidation of thioanisole at room temperature and under an air atmosphere. Abstract : Herein, we demonstrated a highly efficient photocatalytic sulfide oxidation reaction at ambient conditions without a sacrificial reagent or redox mediator, by using Co(NO3 )2 /covalent organic framework nanoparticles as a photocatalyst.